Molecular and Immunohistochemical Classification of Extrapulmonary Small Cell Neuroendocrine Carcinomas: A Study of 181 Cases - Pavlíčková, Klára; Hojný, Jan; Waldauf, Petr; Švajdler, Marián; Dundr, Pavel; Fabian, Pavel; Krkavcová, Eva; Dvořák, Jiří; Michálková, Romana; Zambo, Iva Staniczková; Hájková, Nikola; Flídrová, Miroslava; et al. (Laboratory investigation; a journal of technical methods and pathology, 2025)
Extrapulmonary small cell neuroendocrine carcinoma (EP-SCNC) is a rare malignancy with a poor prognosis. Most patients with EP-SCNC have metastatic disease upon presentation, and their average overall survival (OS) is less than 12 months. Our study aimed to conduct a complex analysis of EP-SCNC. One hundred eighty-one EP-SCNC tissue samples were subjected to a complex analysis. One hundred fifty-five tumors were pure EP-SCNC, whereas 26 were combined tumors. Immunohistochemistry for ASCL1, NEUROD1, YAP1, POU2F3, Rb1, p53, cyclin D1, p16, PTEN, DLL3, PD-L1, CD56, synaptophysin, chromogranin A, and INSM1 was performed, and 128 samples were analyzed molecularly using next-generation sequencing, comprising DNA and RNA analyses. Detailed results on immunohistochemical and molecular analyses were provided for each primary origin of EP-SCNC separately. Median survival for the whole cohort of patients was 8.94 months. Patient age (≥70 years), tumor mutational burden <15, and TP53 and BRCA2 mutations were negative prognostic factors. High expression of ASCL-1 was associated with shorter OS, whereas high expression of YAP1 was associated with longer OS. Patients with genitourinary tumors had significantly better OS than those with gastrointestinal tract EP-SCNC tumors. Rb1 expression loss was detected more often in genitourinary tract SCNCs. In contrast, p16 overexpression was found more often in genitourinary tract SCNCs. POU2F3 expression was detected more often in combined tumors, whereas NEUROD1 was detected more often in pure EP-SCNC. Regarding "druggable markers," DLL3 was expressed in 66% of tumors and PD-L1 in 17.4%. Detailed analyses of different prognostic and predictive markers are needed to better understand EP-SCNC biology and create more personalized therapy to improve patient prognosis.
Keywords: yes-associated protein 1; Humans; lidé středního věku; Biomarkers, Tumor; neurogenic differentiation factor 1; Female; Aged; Carcinoma, Small Cell; dospělí; senioři; lidé; Immunohistochemistry; Carcinoma, Neuroendocrine; imunohistochemie; neuroendokrinní karcinom; nádorové biomarkery; malobuněčný karcinom; Adult; POU class 2 homeobox 3; ženské pohlaví; Male; Middle Aged; prognóza; tumor mutation burden; Aged, 80 and over; achaete-scute homolog 1; senioři nad 80 let; extrapulmonary neuroendocrine small cell carcinoma; mužské pohlaví; Prognosis